Sustained virological response and drug resistance among female sex workers living with HIV on antiretroviral therapy in Kampala, Uganda: a cross-sectional study. (2nd July 2019) - Namale, Gertrude; Kamacooko, Onesmus; Bagiire, Daniel; Mayanja, Yunia; Abaasa, Andrew; Kilembe, William; Price, Matt; Ssemwanga, Deogratius; Lunkuse, Sandra; Nanyonjo, Maria; Ssenyonga, William; Mayaud, Philippe; et al.
Abstract : Objectives: We assessed the prevalence and risk factors associated with virological failure among female sex workers living with HIV on antiretroviral therapy (ART) in Kampala, Uganda. Methods: We conducted a cross-sectional study between January 2015 and December 2016 using routinely collected data at a research clinic providing services to women at high risk of STIs including HIV. Plasma samples were tested for viral load from HIV-seropositive women aged ≥18 years who had been on ART for at least 6 months and had received adherence counselling. Samples from women with virological failure (≥1000 copies/mL) were tested for HIV drug resistance by population-based sequencing. We used logistic regression to identify factors associated with virological failure. Results: Of 584 women, 432 (74%) with a mean age of 32 (SD 6.5) were assessed, and 38 (9%) were found to have virological failure. HIV resistance testing was available for 78% (28/38), of whom 82.1% (23/28) had at least one major drug resistance mutation (DRM), most frequently M184V (70%, 16/23) and K103N (65%, 15/23). In multivariable analysis, virological failure was associated with participant age 18–24 (adjusted OR (aOR)=5.3, 95% CI 1.6 to 17.9), self-reported ART non-adherence (aOR=2.6, 95% CI 1.2 to 5.8) and baseline CD4+ T-cell count ≤350 cells/mm 3 (aOR=3.1, 95% CI 1.4 to 7.0). Conclusions: A relatively low prevalence of virological failure but high rate of DRM was found in this population at high risk of transmission. Younger age, self-reported ART non-adherence and low CD4+ T-cell count on ART initiation were associated with increased risk of virological failure.